Evidence-Based Medicine in Plastic Surgery: From Then to Now. Issue 4 (7th September 2021) - Rohrich, Rod J.; Cohen, Joshua M.; Savetsky, Ira L.; Avashia, Yash J.; Chung, Kevin C.
Abstract : Summary: Evidence-based medicine, as described by Dr. Sackett, is defined as the "conscientious, explicit, and judicious use of current best evidence, combined with individual clinical expertise and patient preferences and values, in making decisions about the care of individual patients." In the late 2000s, seminal articles in Clinics in Plastic Surgery and Plastic and Reconstructive Surgery introduced evidence-based medicine's role in plastic surgery and redefined varying levels of evidence. The American Society of Plastic Surgeons sponsored the Colorado Springs Evidence-Based Medicine Summit that set forth a consensus statement and action plan regarding the increased incorporation of evidence-based medicine into the field; this key meeting ushered a new era among plastic surgeons worldwide. Over the past decade, Plastic and Reconstructive Surgery has incorporated evidence-based medicine into the Journal through an increase in articles with level I and II evidence, new sections of the Journal, and the introduction of validated tools to help authors perform prospective and randomized studies that ultimately  led to best practices used today. Plastic surgery is a specialty built on problem-solving and innovation, values starkly in-line with evidence-based medicine. Evidence-based medicine is becoming more ingrained in our everyday practice and plastic surgery culture; however, we must work actively to ensure that we continue this trend. In the next decade, we will possibly see that level I and II evidence articles start to inhabit many of our journal issues.